2013
DOI: 10.1080/02687038.2013.866209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonological neighbourhood on the treatment of naming in aphasia

Abstract: Background: Phonological treatments to improve naming ability in aphasia focus on restrengthening connections within the phonological system. Nonetheless, the efficacy of phonological treatments is still being explored with particular consideration of cognitive neuropsychological perspectives. Clinicians may also need to consider lexical factors that interact with the word retrieval process. Researchers have shown that phonological neighbourhood density influences normal language recognition and production, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Hendricks and colleagues concluded that phonological neighborhood affected naming ability in their contextual priming paradigm. 27 Specifically, front-matched pictures representing words with high density phonological neighborhoods (i.e., phonologically similar words) were named the most accurately.…”
Section: Traditional Phonological Treatment Approachesmentioning
confidence: 99%
“…Hendricks and colleagues concluded that phonological neighborhood affected naming ability in their contextual priming paradigm. 27 Specifically, front-matched pictures representing words with high density phonological neighborhoods (i.e., phonologically similar words) were named the most accurately.…”
Section: Traditional Phonological Treatment Approachesmentioning
confidence: 99%
“…Shorter word length (Castro et al, 2020;Nickels & Howard, 1995 and denser phonological neighborhoods (Gordon, 2002;Gordon & Dell, 2001;Laganaro et al, 2006;Middleton & Schwartz, 2011) have also emerged as facilitators of word retrieval in aphasia. Though these effects have been examined outside the context of treatment, one study (Hendricks et al, 2014) recently showed that words with high phonological neighborhood density benefitted the most during a phonological treatment when compared to low density words and phonological control words. Nevertheless, no study has systematically examined how these psycholinguistic properties might influence naming abilities and response to treatment in bilingual aphasia.…”
Section: Stimulus-level Factors Modulating Language Treatment Outcome...mentioning
confidence: 99%